Collection Rates and Morphology of Equine Oocytes Obtained from Immature Follicles after Treatment with Equine Pituitary Extract (EPE) and Human Chorionic Gonadotropin - Blanco, Ieda D. P. [UNESP]; Devito, Liane G. [UNESP]; Ferreira, Heder N. [UNESP]; Araujo, Gustavo H. M. [UNESP]; Fernandes, Claudia B. [UNESP]; Alvarenga, Marco Antonio [UNESP]; Landim-Alvarenga, Fernanda da Cruz [UNESP] (Elsevier B.V., 2009)
This study examined the effect of treating mares with equine pituitary extract (EPE) in combination with human chorionic gonadotropin (hCG; EPE/hCG) on the recovery rate of immature oocytes by ovum pick-up (OPU) and on oocyte morphology. Ten mares were subjected to each of two treatments in a random sequence: superstimulated with EPE (25 mg, twice daily) and treated with hCG (2,500 IU) or control (no exogenous treatment). The cytoplasmic morphology of oocytes recovered was evaluated through transmission electron microscopy. Follicular fluid was collected at aspiration for progesterone analysis, which was performed by radioimmunoassay. The EPE/hCG did not increase the oocyte recovery rate from immature follicles when compared with the controls (15.5% and 16.7%, respectively). A significantly higher oocyte recovery rate per mare was observed (70% versus 50%). However, precocious granulosa cell expansion was observed with EPE/hCG treatment in contrast to the control (64.4% and 33% of follicles with expanded cumulus, respectively), and increased intrafollicular progesterone concentration was also seen (158.80 ng/mL versus 82.05 ng/mL). The ultrastructural analysis of oocytes from both groups showed morphologic features related to immaturity. Numerous vesicles containing cortical granules were found, distributed in clusters into the cytoplasm, and junctional complexes were still seen between oocyte and granulosa cells. In conclusion, EPE/hCG treatment induced some follicular modifications, but the recovery rate was not increased. All oocytes examined presented signs of immaturity.
Keywords: OPU; Equine; Oocytes; EPE; hCG